Birth of an empire - Marshall, Robert (Princeton : Films for the Humanities and Sciences [production company] ; Kuala Lumpur : Visual Resources [distributor], 1994)
This program examines how Genghis Khan emerged from obscurity, united the Mongol tribes under his banner, and transformed an obscure nomadic people into the most formidable fighting machine
Director for NHK, Nobuya Yamamoto, Ganji Eto, Tomohidae Terai ; executive producer, Takashi Inoue
Narrator: Sean Barrett
Keywords: Mongols -- History; Mongolia